Safety and tolerability of as-needed nalmefene in the treatment of alcohol dependence: results from the Phase III clinical programme - Brink, Wim van den; Mann, Karl (Expert opinion on drug safety, 2015)
Objective: To investigate safety and tolerability of nalmefene for reduction of alcohol consumption in alcohol-dependent patients. Methods: Pooled data from three randomized, placebo-controlled studies (two 6-month; one 12-month) of 18 mg nalmefene (as-needed use) in alcohol-dependent patients looking at the total population (placebo n = 824, nalmefene n = 1123) and patients with high/very high drinking risk levels at screening and randomization (target population: placebo n = 374, nalmefene n = 450). Results: In the study, 62.7% of patients on placebo and 74.7% on nalmefene in the total population had treatment-emergent adverse events (TEAEs). Fourty-seven (5.9%) on placebo and 149 (13.0%) on nalmefene dropped out due to TEAEs. Thirty-five (4.4%) on placebo and 57 (5.0%) on nalmefene had serious adverse events. Tolerability and safety were similar in the target population and total population. Most frequent TEAEs were transient, mainly occurring at treatment initiation. There was no difference in tolerability and safety if nalmefene was taken daily or intermittently; no signal of increased risk of suicide-related behavior with nalmefene. The higher incidence of psychiatric events in the nalmefene group was mainly due to the TEAE of confusional state. Conclusions: Although there was a higher incidence of TEAEs and TEAEs leading to dropout, nalmefene was well-tolerated and no major safety issues were identified.
Gesehen am 21.11.2017